Health Workers Motivation in the Implementation Early Initiation of Breastfeeding - Eka Nur Fitriana; Yuni Puji Widiastuti; Istioningsih Istioningsih (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Early initiation of breastfeeding is the right of every baby. The obligation for health workers who provide assistance during labor is giving early initiate breastfeeding. However, not all babies are given an IMD and not all health workers do this. The causes are the lack of motivation of health workers in implementing early initiation of breastfeeding. The purpose of this study was to determine the motivation of health workers in implementation early initiation of breastfeeding at RSUD Dr. H. Soewondo Kendal. The research design used is quantitative with descriptive methods. The sample in this study amounted to 28 respondents with a total sampling technique. Instruments in the form of a questionnaire. Data analysis uses univariate. The results showed that the motivation of health workers in implementing Early Breastfeeding Initiation was in the "medium" category as much as 57.1%. Intrinsic motivation of health workers in the implementation of early breastfeeding initiation is mostly done, namely happy when the IMD is successful. Extrinsic motivation of health workers in the implementation of early breastfeeding initiation is mostly done by conducting IMD because there is a policy from the government. This research is expected to be used as input for health workers, especially midwives, in increasing motivation to provide early breastfeeding initiation.